Comportamento sexual de risco em adolescentes escolares - Batista, Fernanda Altermann (2014)
The experience of sexuality during adolescence is considered a normative aspect of adolescence marked by the influence of biological, familial and cultural aspects that will be the pattern of sexual identity and sexual behavior of adolescents. However, many adolescents do not have adequate knowledge and skills to implement safe sexual behavior may lead them to engage in sexual behaviors that create risk to their health. These behaviors are considered risky, and can lead adolescents to have an unwanted pregnancy or getting a sexually transmitted disease. National and international studies identified factors that may influence the development of these behaviors in sexual initiation and management of contraception. The age and education can act as protective factors related to delay of first sexual intercourse. Gender have a strong influence, especially in the management of contraception along with parental support. These factors can influence the choice of contraceptive method used in subsequent sex initiation. Observed few national studies with a focus on relationships between parental support and sexual risk behaviors in adolescents. To address the proposed objectives, this dissertation presents itself divided into two articles. In the first study, a systematic review of literature on sexual risk behavior from national studies were conducted. In the second study, we investigate possible relationships between parental support and sexual risk behaviors and other factors that could be exerting influence these behaviors, in adolescents in public schools. Participated in this study 508 students from elementary and secondary education in public schools in a city in the central region of Rio Grande do Sul. We used to collect data the Brazilian Questionare Phase II which investigating risk and protective factors in adolescents. The adolescents have their first sexual intercourse at about fourteen years old, with a steady partner. During the management of contraception it was found a decrease in the consistent use of condoms during sexual intercourse, particularly by girls who start using the pill as a contraceptive method. These data call attention to the fact that adolescents are preventing themselves from pregnancy and not STDs.